Sistem Pendukung Keputusan Kenaikan Jabatan Menggunakan Metode Profile Matching - Sugiartawan, Putu; Rowa, Heruzulkifli; Hidayat, Nurul (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2018)
Decision Support System is a system that can assist managers in making decisions that are based on the criteria set by the company. Decision Support System helps in the assessment process so it does not happen to be subjective judgment in decision making. Ratings are based on the criteria that have been determined are expected to determine the employee is entitled to a promotion. Many methods can be used in making a decision support system. One method that can be used in making a decision support system that the method Profile Matching. Profile Matching is the process of comparing the profiles of employees with occupational profiles so that the known value of the gap. The smaller the value gap is generated, then the weight value will be even greater gap so that employees the opportunity to get a promotion will be even greater. The results of the calculation with profile matching method in the form of value which ranked based on the largest value. The results of this ranking value will be used as a reference in helping managers to make decisions. Software used in the manufacture of these decision support systems applications with Microsoft Visual Basic 6.0 with MySQL databases.